Saúde mental e fatores emocionais nas campanhas brasileiras da semana mundial de aleitamento materno - Priole, Pâmela [UNESP]; Valle, Leonardo Dalla [UNESP]; Migliorini, Walter José Martins [UNESP] (My University, 2014)
The reduction of child mortality has been the focus of World Breastfeeding Week campaigns. On the other hand, breastfeeding and weaning are considered by psychoanalysis as key moments in the prophylaxis in mental health. Our goal is to investigate how the emotional aspects involved in breastfeeding have been addressed on the promotional material of Brazilian campaigns from 1999 (year of its creation) to 2010. The method adopted was the categorical content analysis and the results indicate that (1) the emotional benefits of breastfeeding are treated superficially, (2) weaning is depleted of its relational dimension (separation), being presented as a chronological and pragmatic concept, based on the introduction of new foods, (3) the term "mental health" is mentioned only once, without a precise definition. The relationship between breastfeeding and emotional development, besides the prophylaxis of mental health, has not been fully exploited in the analyzed campaigns.

Reduzir a mortalidade infantil tem sido o foco das campanhas da Semana Mundial de Aleitamento Materno. Por outro lado, a amamentação e o desmame são considerados pela psicanálise como momentos fundamentais na profilaxia em saúde mental. Nosso objetivo é investigar como os aspectos emocionais envolvidos no aleitamento são abordados no material de divulgação das campanhas brasileiras, de 1999 (ano de sua criação) a 2010. O método adotado foi a análise categorial de conteúdo e os resultados indicam que (1) os benefícios emocionais da amamentação são tratados de modo periférico, (2) o desmame é empobrecido em sua dimensão relacional (separação), sendo apresentado como um conceito pragmático, cronológico e baseado na introdução de novos alimentos, (3) o termo "saúde mental" é mencionado uma única vez e sem definição precisa. O vínculo entre amamentação e desenvolvimento emocional, assim como a perspectiva de profilaxia em saúde mental não foram plenamente exploradas nas campanhas analisadas.
Mental health and emotional factors in brazilian campaigns of world breastfeeding week
Keywords: Breastfeeding; Emotional development; D. W. Winnicott; National campaigns of world breastfeeding week; Weaning; Psicanálise; Desenvolvimento emocional; Semana Mundial de Aleitamento Materno; Desmame precoce